Human COQ9 Rescues a coq9 Yeast Mutant by Enhancing Coenzyme Q Biosynthesis from 4-Hydroxybenzoic Acid and Stabilizing the CoQ-Synthome - He, Cuiwen H.; Black, Dylan S.; Allan, Christopher M.; Meunier, Brigitte; Rahman, Shamima; Clarke, Catherine F. (Frontiers in Physiology, 2017)
Coq9 is required for the stability of a mitochondrial multi-subunit complex, termed the CoQ-synthome, and the deamination step of Q intermediates that derive from para-aminobenzoic acid (pABA) in yeast. In human, mutations in the COQ9 gene cause neonatal-onset primary Q10 deficiency. In this study, we determined whether expression of human COQ9 could complement yeast coq9 point or null mutants. We found that expression of human COQ9 rescues the growth of the temperature-sensitive yeast mutant, coq9-ts19, on a non-fermentable carbon source and increases the content of Q6, by enhancing Q biosynthesis from 4-hydroxybenzoic acid (4HB). To study the mechanism for the rescue by human COQ9, we determined the steady-state levels of yeast Coq polypeptides in the mitochondria of the temperature-sensitive yeast coq9 mutant expressing human COQ9. We show that the expression of human COQ9 significantly increased steady-state levels of yeast Coq4, Coq6, Coq7, and Coq9 at permissive temperature. Human COQ9 polypeptide levels persisted at non-permissive temperature. A small amount of the human COQ9 co-purified with tagged Coq6, Coq6-CNAP, indicating that human COQ9 interacts with the yeast Q-biosynthetic complex. These findings suggest that human COQ9 rescues the yeast coq9 temperature-sensitive mutant by stabilizing the CoQ-synthome and increasing Q biosynthesis from 4HB. This finding provides a powerful approach to studying the function of human COQ9 using yeast as a model.